2010
DOI: 10.1038/modpathol.2010.92
|View full text |Cite
|
Sign up to set email alerts
|

C1q deposition in the renal allograft: a report of 24 cases

Abstract: C1q nephropathy is an uncommon glomerular disease characterized by dominant or codominant mesangial staining for C1q in the absence of systemic lupus erythematosus. There are no series in the literature addressing the significance of C1q deposition in the renal allograft. We retrospectively analyzed 24 patients, most of whom were white (83%) and male (63%), with a mean age at transplant of 31 years. None of the patients were diagnosed with C1q nephropathy in the native kidney or had any features of systemic lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 17 publications
1
26
0
3
Order By: Relevance
“…In addition, C1q was found in DGF and TCMR in peritubular localization but lacking in glomeruli. In contrast, in a small study with 24 patients, mesangial C1q detection by immunofluorescence staining was not restricted to ABMR [38] and information on peritubular C1q localization is lacking. Furthermore, C3c was highest in ABMR biopsies in all investigated compartments, reaching significance in glomeruli.…”
Section: Differences In Level and Site Of Complement Activation In Abmentioning
confidence: 87%
“…In addition, C1q was found in DGF and TCMR in peritubular localization but lacking in glomeruli. In contrast, in a small study with 24 patients, mesangial C1q detection by immunofluorescence staining was not restricted to ABMR [38] and information on peritubular C1q localization is lacking. Furthermore, C3c was highest in ABMR biopsies in all investigated compartments, reaching significance in glomeruli.…”
Section: Differences In Level and Site Of Complement Activation In Abmentioning
confidence: 87%
“…C1q nephropathy is defined as dominant or codominant mesangial staining for C1q without clinical or serological evidence of SLE . Said et al described the C1q deposition in renal allografts, and reported that four of 24 cases in their study exhibited IgG staining intensity similar to that of C1q. Additionally, a mesangial electron‐dense deposit was detected in 82% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…En pacientes trasplantados se ha documentado depósitos de C1q en aloinjerto renal, aunque su prevalencia es baja 0.4%, el papel pronóstico en el paciente transplantado aún no está muy claro [7] En una revisión de Inkeri y cols se menciona que la excesiva activación del complemento y depósitos de C1q en placenta se relacionan con preeclampsia y abortos, a pesar de una evidencia pobre, no descartamos que en la paciente las perdidas recurrentes del embarazo pudieran estar en relación con esta patología [8].…”
Section: Discussionunclassified